The effect of neutrophil-lymphocyte ratio on admission to postoperative intensive care and mortality in elderly patients undergoing hip fracture surgery with spinal anesthesia - Miniksar, Ökkeş Hakan; Kaçmaz, Osman (The European Research Journal, 2021)
Objectives: Hip Fractures (HF) affect the elderly in particular, and are associated with high mortality rates. Most geriatric patients are admitted to Intensive Care Unit (ICU) after HF surgery. In this study, the purpose was to investigate the prognostic value of preoperative NLR (Neutrophil-to-Lymphocyte Ratio) on postoperative ICU admission and mortality in elderly patients with HF. Methods: In the present study, the data of 188 geriatric patients who underwent surgery because of isolated HF (i.e. femur neck and intertrochanteric fracture) were examined retrospectively. The patients over 65 years of age, ASA score 3/4, whose preoperative duration was less than 72 hours, and who underwent spinal anesthesia were included in the study. The patients were divided into two groups as ICU admission (ICU, n = 58), and Non-ICU (Non-ICU, n = 130). The patients were also grouped as Survival (n = 168) and Non-survival (n = 20) according to postoperative mortality rates. NLR values were statistically compared between the groups. Results: The preoperative NLR values of the patients in the ICU Group were significantly higher than those in the Non-ICU Group (p < 0.001). The cut-off value of NLR for ICU admission was found to be 9.65 with 89% sensitivity and 67% specificity in the ROC analysis. The median NLR value was 6.42 (3.55-9.44) in the Survivor Group, and 9.5 (7.23-11.02) in the Non-Survivor Groups (p = 0.015). Conclusions: It was shown in the study that high NLR values in elderly patients may be a risk factor for ICU admission, and for postoperative mortality after HF.